Antioxidant and stabilization activity of a quercetin-containing flavonoid extract obtained from Bulgarian Sophora japonica L. - Mihaylova,Dasha (2013)
This work aimed to study the antioxidant activity of a quercetin-containing flavonoid extract (FQЕ) obtained from Sophora japonica L. flower buds rich in quercetin (91.6%). Radical scavenging activity was analyzed towards the synthetic radicals DPPH and ABTS+ and antioxidant activity was evaluated applying the method of oxygen consumption in a model system containing methyl linoleate. Model food systems of lard and sunflower oil were explored by the application of Rancimat method and chicken as a real food system was investigated by the thiobarbituric acid test. Results showed a high radical scavenging activity and antioxidant capacity of QFE similar to those of the pure flavonoid quercetin.